1998
DOI: 10.1111/j.1365-8711.1998.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-subcluster mergers and the formation of narrow-angle tailed radio sources

Abstract: firstpage-lastpage 1998 document firstpage abstract We have examined the ROSAT PSPC X-ray properties of a sample of 15 Abell clusters containing 23 narrow-angle tailed (NAT) radio galaxies. We find that clusters with NATs show a significantly higher level of substructure than a similar sample of radio-quiet clusters, indicating that NAT radio sources are preferentially located in dynamically complex systems. Also, the velocity distribution of the NAT galaxies is similar to that of other cluster members; these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 58 publications
(82 reference statements)
1
2
0
Order By: Relevance
“…The presence of the two galaxy number density peaks and the elongated X-ray morphology between them strongly suggest that A514 is currently undergoing a binary merger in the NW-SE direction. Previous observations have reported three headtail radio galaxies in A514 (Burns et al 1994;Bliton et al 1998;Govoni et al 2001), which are all classified as spectroscopic members (Owen et al 1995;Katgert et al 1998). With our new uGMRT radio observations, we revealed the bent morphology in these three radio galaxies.…”
Section: A Large-scale Bent Radio Jet In A514supporting
confidence: 50%
“…The presence of the two galaxy number density peaks and the elongated X-ray morphology between them strongly suggest that A514 is currently undergoing a binary merger in the NW-SE direction. Previous observations have reported three headtail radio galaxies in A514 (Burns et al 1994;Bliton et al 1998;Govoni et al 2001), which are all classified as spectroscopic members (Owen et al 1995;Katgert et al 1998). With our new uGMRT radio observations, we revealed the bent morphology in these three radio galaxies.…”
Section: A Large-scale Bent Radio Jet In A514supporting
confidence: 50%
“…Evidence of dynamical substructure was also found with optical spectroscopy of the member galaxies (Oegerle et al 1995). Interestingly, the presence of a narrow-angle tailed radio galaxy may be explained by significant bulk motions in the ICM, as suggested by the statistical analysis of Bliton et al (1998). Finally, Cuciti et al (2015) reported A2142 to have a radio halo.…”
Section: Abell 2142mentioning
confidence: 74%
“…NATs are generally thought to be formed via ram pressure resulting from the high-speed infall or orbital motions of the host galaxy relative to the ICM. However, Bliton et al (1998) suggest that, in many cases, the orbital velocity of the host galaxy is simply not high enough to produce the high degree of bending seen in NATs. They present an alternative scenario of NAT formation due to the host cluster experiencing a merger event.…”
Section: Introductionmentioning
confidence: 99%